The Cluster Approach Application for Economic Ecosystems in the Aspect of the Precision Instrumentation - POKRAS, Olena S.; VOITKO, Serhii V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).26, 2019)
The present study shows the connection between the quality of life, the environmental indicator and gross domestic product per capita, based on purchasing power parity. Economically developed countries tend to turn to a policy of sustainable development, which combines a careful attitude to the natural environment, natural resources and social guarantees for citizens. At the same time, less developed countries pay less attention to the above-mentioned factors. These statements were set by using cluster analysis method. One of the most essential natural resources is water. The population of the Earth is growing exponentially and the presence of a constant amount of fresh water is a serious problem. Evidence of such a problem can be found in the increase in water tariffs for both domestic and industrial use. The purpose of the study is to find the interdependence between social, economic and environmental factors in order to substantiate the expediency of instrumentation solutions application to solve the problem of water resources rational use. For this purpose, losses from errors in measurement of water meters for different groups of consumers in dollar terms, taking into account current tariffs, were analyzed. The necessity of using precision equipment for measuring the volume of used water has been proven. The basic descriptive statistics of quality of life, environmental performance, gross domestic product and tariffs are used. The results constitute an introduction to further and more advanced research at the field of economic ecosystem problems and solutions.